Mengubah Limbah Tanaman Apel Menjadi Pewarna Alami Bernilai Tinggi di Madiredo - Zurinani, Siti; Pradhikta, Dyanningrum; Fatmawati; Wahyu Utama, Aji Prasetya; Setiawan, Romy (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
The utilization of apple plant waste as a natural dye extract is important for the development of creative products using safer dye materials. Madiredo, as an apple cultivation economic zone, produces waste from the apple processing process. This apple plant waste can be utilized as a high-value dye extract using ecoprint techniques or combined with batik. This initiative is expected to foster the creativity of women in the Madiredo village PKK (Family Welfare Movement) to achieve economic independence. In further development, it will also be innovated with Madiredo's distinctive motifs while highlighting the cultural potential of Madiredo. Additionally, the use of natural dyes in textile products can address the issues arising from the use of synthetic dyes, which, unbeknownst to many, have the potential to cause environmental pollution. Furthermore, this serves as a means of cultural promotion and branding for Madiredo Village. The outcomes of this partnership program include the utilization and processing of apple plant waste and Madiredo Village's natural resources, as well as the development of environmentally friendly textile product designs to enhance the economic well-being of the partner community. Additionally, the results of this community service program are presented not only in the form of a final report but also as scientific publications in national journals or proceedings. Keywords: natural dyes; products; branding; waste; motifs; women